Effect of Covid on Gaster Intestinal Tract and its Signs and Symptoms - Rana Muhammad Suhail Khan, Muhammad Afham Shahid, Shoaib Akram, Ammara Riaz (Pakistan Journal of Medical & Health Sciences, 2022)
The aim of this descriptive case series was to determine the frequency of various gastrointestinal symptoms of the COVID-19 patients along with the respiratory symptoms. Secondary outcome was to determine the effect of various co-morbid conditions and various sign and symptoms on the length of hospital stay and outcome of disease Material: In this descriptive case series type study, carried out in the COVID ward in the Jinnah Hospital, Lahore, all patients diagnosed with COVID-19 by consultant physician in the out-patient department and ward were included. Written informed consent was taken from all the participants of the study after explaining the primary objective of the study. The study was carried out from 01-07-2019 to 31-12-2019. Primary objective of this study was to determine the various gastrointestinal symptoms of the COVID-19 patients along with the respiratory symptoms Results: Among the 386 patients enrolled in the study, 60% were male and 40% were female. Mean age of the patients was 54.14 SD 16.3 years, with around 71% cases of age above 45 years. Abdominal pain, anosmia and diarrhea were the most common GI complaints. Over all, 26% of the patients of COVID had GI symptoms. Conclusion: GI complaints such as anorexia, nausea, vomiting, diarrhea, and abdominal cramping have been documented in COVID-19 individuals even in the absence of respiratory problems. As a result, COVID-19 disease must be explored in individuals who have mostly GI complaints.